Catalityc Converter Jenis Katalis Pipa Tembaga Berlubang Untuk Mengurangi Emisi Kendaraan Bermotor - Ali Mokhtar (Jurnal Gamma, 2012)
Catalityc Converter Jenis Katalis Pipa Tembaga Berlubang Untuk Mengurangi Emisi Kendaraan Bermotor Ali MokhtarStaf Pengajar Jurusan Teknik Mesin, Fakultas TeknikUniversitas Muhammadiyah MalangEmail : alimokhtar011@gmail.com, balimokhtar06@yahoo.co.idABSTRACTDecreased levels of exhaust emissions are influenced by the catalyst material and shape of the catalyst, the catalyst model of perforated pipes showed oxidation and reduction process goes well, it is shown that the levels of CO2 decreased by 49.7338%, while CO emissions fell by 36.904% and the emissions HC decreased by 28.354%. In general installation catalityc hollow pipe catalytic converter type can reduce exhaust emissions compared with using ctalityc converter.Key Word : copper pipe perforated catalyst